Impaired Sensitivity to Thyroid Hormones Is Associated With Elevated Blood Glucose in Coronary Heart Disease - Yu, Lu; Li, Zhu; Yang, Rongrong; Pan, Guangwei; Cheng, Qi; He, Yuanyuan; Liu, Yijia; Liu, Fanfan; Ma, Mei; Yang, Tong; Wang, Yang; Su, Jinyu; et al. (Frontiers in Endocrinology, 2022)
Context Thyroid hormones influence glucose homeostasis through central and peripheral regulation. To date, the association between thyroid hormone sensitivity and elevated blood glucose (EBG) in patients with coronary heart disease (CHD) remains unknown. The purpose of this study was to investigate the association between thyroid hormone sensitivity and risk of EBG in patients with CHD, and to further explore their association in different sexes and ages. Methods This large multicenter retrospective study included 30,244 patients with CHD (aged 30–80 years) between 1 January 2014 and 30 September 2020. Parameters representing central and peripheral sensitivity to thyroid hormones were calculated. Central sensitivity to thyroid hormones was assessed by calculating the Thyroid Feedback Quantile-based Index (TFQI), Thyroid-stimulating Hormone Index (TSHI), and Thyrotropin Thyroxine Resistance Index (TT4RI), and Parametric Thyroid Feedback Quantile-based Index (PTFQI); peripheral sensitivity to thyroid hormones was evaluated using the ratio of free triiodothyronine (FT3) /free thyroxine (FT4). Taking normal glucose tolerance (NGT) as a reference, logistic regression was used to analyse the relationship between central and peripheral thyroid hormone sensitivity and EBG in patients with CHD. Results Among the 30,244 participants, 15,493 (51.23%) had EBG. The risk of EBG was negatively correlated with TSHI (OR: 0.91; 95%CI: 0.91 to 0.92; P < 0.001), TT4RI (OR: 0.99; 95% CI: 0.99 to 0.99; P<0.001), TFQI (OR: 0.82; 95%CI: 0.80 to 0.84; P <0.001) and PTFQI (OR: 0.76; 95%CI: 0.74 to 0.78; P<0.001). Compared to males and patients aged 60 and below, the OR value for EBG was lower in females and in patients aged over 60 years old. Conversely, EBG risk was positively associated with FT3/FT4 (OR: 1.08; 95% CI: 1.07 to 1.09; P <0.001) and in the sex-categorized subgroups, males had higher OR values than females. Conclusions This study showed that thyroid hormone sensitivity is significantly associated with EBG in patients with CHD. This association is higher in females than in males, and the association in those aged over 60 years old is higher than that in patients aged 60 years and below.